Tarybų Lietuvos bibliotekų darbuotojų persekiojimas ir žudymas hitlerinės okupacijos metais - Sinkevičius, Klemensas (Knygotyra, 1982)
According to the plans of German invaders the system of education and the cultural establishments in Lithuania had been totally destroyed. The libraries of trade unions and other organizations were eliminated, most of mass, scientific and school libraries were closed down. The fascists exercised savage reprisals towards the library workers of the Soviet period, they were discharged from office, persecuted, arrested and sent to concentration camps. Scores of librarians were executed.